GROWTH EVALUATION OF RED MERANTI SPECIES IN RESTORATION AREA OF GUNUNG DAHU RESEARCH FOREST, BOGOR - Eggy Nugraha Ariansyah; Prijanto Pamoengkas; Rizki Ary Fambayun; Henti Hendalastuti Rachmat (Jurnal Penelitian Hutan dan Konservasi Alam, 2020)
The use of local species for revegetation activities is expected to accelerate the natural regeneration to increase the biodiversity in restoration efforts of disturbed areas. This study used several parameters to observe the growth of 20-years old stand S. pinanga and S. platyclados, including diameter, total tree height, Mean Annual Increment (MAI), % of fruiting trees, Leaf Area Index (LAI), altitude, and slope. The study results were analyzed using one-way variance analysis (ANOVA) and Duncan test with a 95% confidence level. The results showed that S. platyclados significantly had a higher diameter (32.7 cm), height (19.1 m), and mean volume (0.43 m3) compared to S. pinanga. The growth of S. platyclados, which locally known as meranti bukit is strongly supported by conditions in Gunung Dahu Research Forest, which has an altitude of about 800 m.asl. On the other hand, S. pinanga, as lowland species, showed lower growth compared to S.platyclados.